Herramientas y técnicas de administración financiera para la Cooperativa de Ahorro y Crédito COOPYMEC del Cantón Macará - Paucar Jaramillo, Jenny Alejandra (2016)
This work called "Tools and Techniques Financial Management for Cooperative Savings and Credit COOPYMEC macará canton", aims to raise awareness of the importance of implementing financial management tools, thus contributing to the financial function of the Cooperative make the right decisions regarding the efficient management of economic resources. For the development of this research it was necessary to propose goals and vertical analysis, horizontal, PEARLS Monitoring System, breakeven for the periods 2012 and 2013, and with regard to financial planning budgets and projected statements are made. To fulfill the first objective vertical and horizontal analysis of both the Statement of Financial Position and the State Economic Situation of 2012- 2013 periods was made; 2013 where the assets are of $ 195,518.23, so it was determined that the structure of the credit union is mostly made up of borrowings; $ 13,092.28 liabilities - - just as the variations in the periods studied, where the assets are set presents variations of the assets of $ 20,572.12 $ 7,479.84; revenues show a variation of - $ 10,193.58 and expenses - $ 8,122.96. 6 The second goal was achieved by applying financial indicators PEARLS Monitoring System in 2012-2013 periods with it was learned that the entity has a solvency of 74.55% and 82.69%, 86.06% and liquidity of 89.60%, non-performing assets with 112.35% and 104.84%, and the yield of 23.09% and 19.58% results indicating that the Cooperative has poor management of resources which does not It allows you to get enough income to grow in the financial market. In the third objective breakeven was conducted to determine the level of income that should produce the Cooperative, to cover their costs and expenses, so that for the period 2013; the entity to generate $ 39,382.27 equivalent to 99.57% may cover its financing costs and expenses, ie neither win nor lose. In the fourth objective income forecasts they were developed through placements of its loan portfolio and expenditure budget through its loans and other operating expenses this information allowed cash budgeting and know the resources that the entity expects to obtain in year to finance the costs; obtaining final cash flow of $ 45,428,79 in 2014 and $ 55.382,00 for 2015. In the fifth goal projected financial statements for the periods 2014 and 2015 were conducted, giving as a result of asset $ 230,163.73 to $ 269,602.68 in 2014 and 2015, liabilities will be $ 144.789,30 and $ 161.422,02 with assets of $ 85.374,44 for the year and $ 108.180,67; The 7 State Economic Situation reflects net income of $ 7,446.26 and $ 13,072.39 for the years 2014 and 2015 respectively. Finally it is concluded that the financial institution during the periods 2012 and 2013, has low level of loans, deposits and weak credit policy, which does not allow you to get adequate returns, so it is necessary the Governing taken the necessary corrective and manages to improve its administrative and financial management with the aim that the cooperative can create value and thus provide more and better services to the community.